2004
DOI: 10.1023/b:jots.0000038482.53911.01
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic growth in child survivors of a road traffic accident

Abstract: Although the negative consequences of trauma have been well researched and described, posttraumatic growth has only recently come to the attention of researchers. This paper considers whether children (aged 7-18 years) who have been involved in a road traffic accident can experience posttraumatic growth outcomes. From 158 children who took part in an interview, qualitative analysis of interview notes found that 67 (42%) reported some aspect of posttraumatic growth, most notably in terms of their philosophy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
83
0
8

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(103 citation statements)
references
References 23 publications
12
83
0
8
Order By: Relevance
“…We identified 17 studies examining PTG in parents of children with pediatric disease 5,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] (see Table 1), 7 studies that demonstrated PTG or benefit finding in children with pediatric disease [42][43][44][45][46][47][48] (see Table 2), and 2 that included both parents and pediatric patients. 49,50 We summarize the findings from these studies in the nine components of our conceptual model of SPI-PTG: (1) the nature and subjective experience of the traumatic event, (2) trauma and the disruption of a personal worldview, (3) PTG as rebuilding or reshaping this worldview, (4) elements of SPI-PTG, (5) cognitive processing underlying SPI-PTG, (6) affective processing underlying SPI-PTG, (7) posttraumatic afterevents, (8) individual characteristics affecting SPI-PTG, and (9) social support affecting SPI-PTG (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We identified 17 studies examining PTG in parents of children with pediatric disease 5,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] (see Table 1), 7 studies that demonstrated PTG or benefit finding in children with pediatric disease [42][43][44][45][46][47][48] (see Table 2), and 2 that included both parents and pediatric patients. 49,50 We summarize the findings from these studies in the nine components of our conceptual model of SPI-PTG: (1) the nature and subjective experience of the traumatic event, (2) trauma and the disruption of a personal worldview, (3) PTG as rebuilding or reshaping this worldview, (4) elements of SPI-PTG, (5) cognitive processing underlying SPI-PTG, (6) affective processing underlying SPI-PTG, (7) posttraumatic afterevents, (8) individual characteristics affecting SPI-PTG, and (9) social support affecting SPI-PTG (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Posttraumatic growth is not simply a return to baseline from a period of suffering; instead it is an experience of improvement that, for some individuals, is deeply profound [44][45][46][47][48][49][50][51][52].…”
Section: Post-traumatic Growthmentioning
confidence: 99%
“…In a recent qualitative study, Salter and Stallard (2004) found that 42% of children interviewed reported that they experienced either growth in interpersonal relationships and/or greater appreciation of life after a traumatic event. These findings suggest that variability for this construct does exist for children.…”
mentioning
confidence: 99%